2005
DOI: 10.1074/jbc.m411064200
|View full text |Cite
|
Sign up to set email alerts
|

Activation of STAT3/Smad1 Is a Key Signaling Pathway for Progression to Glomerulosclerosis in Experimental Glomerulonephritis

Abstract: Mesangial cell proliferation is a significant event in the development of progressive glomerular injuries. However, the issue of how cell proliferation is involved in the development of glomerulosclerosis is unclear. Recently, we showed that the overexpression of type IV collagen (Col IV), a major component of mesangial extracellular matrix, is transcriptionally regulated by Smad1 in diabetic glomerulosclerosis. In this study, we have demonstrated the effect of the administration of an anti-platelet-derived gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 31 publications
2
38
0
1
Order By: Relevance
“…Interestingly, recent studies have also shown involvement of ALK1/Smad1 pathways in kidney and liver fibrosis. Elevated expression of Smad1 protein was observed in human diabetic kidney and in animal models of diabetic nephropathy (37)(38)(39). In addition, Smad1 was shown to directly up-regulate expression of the collagen type IV gene in mesangial cells (37).…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, recent studies have also shown involvement of ALK1/Smad1 pathways in kidney and liver fibrosis. Elevated expression of Smad1 protein was observed in human diabetic kidney and in animal models of diabetic nephropathy (37)(38)(39). In addition, Smad1 was shown to directly up-regulate expression of the collagen type IV gene in mesangial cells (37).…”
Section: Discussionmentioning
confidence: 95%
“…While the specific interactions between ALK-5 and ALK-1 are still not fully elucidated, there is evidence that the relative ratio of these 2 receptor subtypes regulates the switch between proliferation and differentiation of endothelial cells (15). However, recent studies have also shown that the ALK-1/Smad1 pathway may play a role in kidney fibrosis (29)(30)(31). Furthermore, TGF␤ signaling via activation of the ALK-1/Smad1 pathway and subsequent up-regulation of the Id1 gene have been shown to contribute to transdifferentiation of hepatic stellate cells into myofibroblasts (32).…”
Section: Smad1 Signaling Pathway In Ssc 2535mentioning
confidence: 99%
“…In breast cancer cells and epithelial cells, STAT3 may modulates MEK5 and HSP27 protein expression [7,8]. In addition, STAT3 signaling may regulate the expression of MMP [4,[9][10][11][12], VEGF [4,11,12], and Smad [13,14]. However, STAT3-regulated genes are still unclear in HCC, so in this study, we investigated the STAT3-regulated genes in HCC cells.…”
mentioning
confidence: 99%